Mathematical literacy ability of 9th grade students according to learning styles in Problem Based Learning-Realistic approach with Edmodo - Wardono, Wardono; Mariani, Scolastika; Rahayuningsih, Rista Tri; Winarti, Endang Retno (Unnes Journal of Mathematics Education, 2018)
This study aims to determine the difference and increase of the mathematical literacy ability using PBL-PRS-E, PBL-PS and scientific approach, and to find out difference of the mathematical literacy ability between learning styles. This study belongs to quantitative research. The population in this study are 9th grade students SMP Negeri 1 Majenang, Cilacap academic year 2016/2017. This study uses a quasi-experimental design with pretest-posttest control group design. Then, methods of the study are test, questionnaire, and documentation. Data analysis was performed by one way anova, two way anova, and increase in the gain normalized. The results of the study are (1) the mathematical literacy ability of students in the experimental group 1 is better than the mathematical literacy ability of students in the experimental group 2 and control group, (2) there is no difference in the mathematical literacy ability between learning styles, (3) there is no interaction between the mathematical literacy ability based learning models and student's learning styles, and (4) ithe increase of students’ mathematical literacy ability in the experimental group 1 is better than in the control group but less than the increase of stuednts’ mathematical literacy ability in the experimental group 2. Eventually, this study suggests that 9 grade mathematics teacher in SMPN 1 Majenang can use PBL-PRS-E model to improve the learning result and mathematical literacy ability of students.